Peningkatan Kompetensi Web Design Peserta Didik Menggunakan Metode “Rekam Layar” Di LKP Elite English School - Nurfitri, Khoiru (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
There are 3 aspects of competency that must be achieved by students of computer programs in Elite English school of Ponorogo. The 3 aspects include knowledge, skills and attitudes. In Web Design class of computer programs the average student only excels at one aspect of competency. The unachievement is due to the lack of direct observation by the instructor which causes students to not follow the practice in full. The instructor has difficulty if they have to accompany each student directly because of the limited time and many students in the class. This study aims to apply the rekam layar method so that students are able to achieve all three aspects of competence. The screen recording method is a method that aims to make observations of students using computer software. This study uses the method of direct observation and interviews which lasted for two months. Rekam Layar learning method has been proven to be able to help students personally observe the process effectively. Student competency can be increased using the Rekam Layar learning method.